A estigmatização dos usuários de substâncias psicoativas: concepções internalizadas - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The abusive use of psychoactive substances tends to be approached from an hegemonic, moralistic, judicial, exclusionary and institutional. Such facts culminate in a stigmatizing, prejudiced and discriminatory social construction about the users of psychoactive substances. The objective of this work was to demonstrate the stigmatization experienced by users of psychoactive substances, based on the reports of users, workers and the manager of a Psychosocial Care Center. It consists of a qualitative and exploratory research with a participatory character. The gathering of data took place through Focus Groups with users and workers, and semi-structured individual interview with the manager. In users' statements, workers and the manager there are profound marks of structural stigma and depersonalizing, constructed and legitimized by a society that produces deliberately unkempt and dissonant beings in the face of hygienized and neoliberalists. It is necessary to increase the discussions on this theme, since the social stigmatization of users of psychoactive substances takes root, exclusions, violations of rights and creation of barriers. In this way, reducing spaces for the production of subjectivities of this population.
The stigmatization of users of psychoactive substances: internalized conceptions
Keywords: Saúde mental coletiva; Toxicomania; Estigma social; Saúde mental; Mental health; Social stigma; CNPQ::CIENCIAS DA SAUDE